Double-walled pots boost tree establishment in arid regions - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
A new device consisting of a double-walled earthen pot called a ''jaltripti'' has been developed to help the establishment of trees in arid regions, where there are extremes of temperature, scanty and erratic rainfall and sandy soils which are low...